Functional nickel-vanadium alloy coatings - Dzheniuk, Anatolii Volodymyrovych; Zhelavska, Yu. A.; Rudneva, S. I. (CPN Publishing Group, 2023)
Nickel-vanadium alloy coating was electrodeposited from sulfate electrolyte. The functional properties of the resulting coating were studied, including both mechanical (microhardness) and catalytic (for the hydrogen evolution reaction) properties. Based on research results, electrodes with nickel-vanadium coating, can be recommended as energy-saving cathode material for the electrochemical production of hydrogen.
Keywords: functional materials; electrocatalytic activity; microhardness; Ni-V coating; overpotential